(untitled) (Research, Society and Development, 2020)
Objective: To analyze the temporal trend of notified cases of rape registered in the state of Rio Grande do Sul, between the years 2009 to 2017. Method: This is a quantitative, descriptive study, using secondary data collected in DataSUS, through the following strategy: “Epidemiological diseases and morbidity”, with an emphasis on “diseases and health problems – Domestic, sexual and / or other violence”, highlighting rape cases. A time frame from 2009 to 2017 was used in the state of Rio Grande do Sul. Data were presented by relative frequency, absolute and Pearson’s correlation, using the SPSS version 22.0 program. Results: Notifications for females grew significantly over the nine years analyzed (Cl = 0,683, p = 0,042). The reported cases were more prevalent for females (83,71%), under 14 years old (64,37%), with incomplete elementary education (46,79%) and White (74,26%).Conclusion: Even with the increase and the stronggender relation implicated in the cases of rape in Rio Grande do Sul, these results reveal part of the problem, still very underreported.